Adobe Premiere Pro CC : learn video editing in Premiere Pro (Packt Publishing, 2018)
"Get started with Adobe Premiere Pro today and learn how to video edit! This course is an introduction into video editing using Adobe Premiere Pro CC. It will take you from the very beginning of opening Premiere Pro CC and learning the various panel windows to editing clips together, audio work, color correction, creating sequence presets, titles, keyboard shortcuts, exporting and much more! Your instructor for this course is Will Bartlett. He has been professionally editing since 2004. He is the founder of an established video production company in Toronto and has edited well over 1000 projects. Our team will be available to answer any questions as well as help you with any issues you may come across while making your way through the course. Even if you don't have Adobe Premiere Pro CC you can still take advantage of this course by downloading a free 30 day trial from Adobe, on their website. All you need to do is create a free account with them, it only takes a minute and you will then be able to start downloading Premiere Pro."--Resource description page